Efficacy and safety of camrelizumab plus famitinib in patients with previously treated non-small-cell lung cancer: a single-arm, phase II trial - Ming Gao; Xia Zhang; Huan Yan; Yan Zhao; Fang Yuan; Decong Sun; Xuejiao Yang; Yanfang Ju; Lijie Wang; Haitao Tao; Luyuan Tian; Changhong Zhao; et al. (Therapeutic Advances in Medical Oncology, 2025)
Background: For non-small-cell lung cancer (NSCLC) patients who progressed after first-line chemotherapy, immunotherapy targeting programmed cell death (ligand) 1 has shown promising activity. However, the activity is relatively limited in patients harboring epidermal growth factor receptor (EGFR) mutations. Objectives: This study aimed to evaluate the efficacy and safety of camrelizumab plus famitinib in previously treated patients with locally advanced and metastatic NSCLC. Design: A single-center, single-arm, phase II study. Methods: Previously treated patients with locally advanced and metastatic NSCLC were enrolled to receive camrelizumab (200 mg, administered intravenously every 3 weeks) and famitinib (20 mg, administered orally once daily). Patients harboring EGFR mutation genes had received at least one EGFR tyrosine kinase inhibitor and no more than two lines of chemotherapy regimen before the enrollment. The other patients had progressed on first-line chemotherapy with or without immunotherapy before the enrollment. The primary endpoint was the objective response rate (ORR) per RECIST v1.1 by the investigator. Results: Our study encompassed 23 NSCLC patients between October 2019 and October 2022. For all patients, the confirmed ORR was 30.4%, and the disease control rate was 95.7%. The median progression-free survival (PFS) was 6.9 months (95% CI: 4.9 months–not reached). The median overall survival (OS) was not reached. 1- and 2-year OS rates were 85.6% (95% CI: 71.8%–100.0%) and 56.8% (95% CI: 37.7%–85.7%). Especially, for the 6 patients with EGFR genetic aberrations, the confirmed ORR was 33.3%, the median PFS was 10.3 months (95% CI: 1.8–18.8 months), and the median OS was 20.3 months (95% CI: 0.8–39.8 months). The most common grade 3 and above treatment-related adverse events were platelet count decreased, white blood cell count decreased, and hypertension. No unexpected adverse events were reported. Conclusion: Camrelizumab plus famitinib demonstrated encouraging clinical activity with a manageable safety profile in previously treated patients with locally advanced and metastatic NSCLC. The results warranted further validation. Trial registration: Chinese Clinical Trial Registry identifier: ChiCTR1900026641.